Let's find out about safety - Shapp Martha; Shapp, Charles; Bentley Carolyn (New York : Watts, 1975)
Discusses how to avoid accidents by practicing safety rules.
Keywords: Accidents -- Prevention -- Juvenile literature; Safety education -- Juvenile literature; Safety